IMPLEMENTASI PROGRAM KARTU TANI TERHADAP KETERSEDIAAN PUPUK 2021 DI DESA TEGALMOJO, KECAMATAN TEGALSIWALAN, KABUPATEN PROBOLINGGO - Imam Sucahyo,; Husni Mubaroq,; Mohammad Dwi Febriyanto, (Journal of Innovation Research and Knowledge, 2022)
The policy for distributing Farmer Cards in Probolinggo Regency continues to be carried out. However, so far it has not been able to achieve the target. There are still many cards that have been printed but have not been distributed. The distribution of farmer cards is carried out in stages. In accordance with the availability of cards that are ready to be distributed to farmers registered in the Electronic Definitive Plan for Group Needs (E-RDKK). One of the beneficiaries of Kartu Tani assistance is Tegalmojo Village, Tegalsiwalan District, Probolinggo Regency, which so far has only distributed 20 copies, which should have been 100. The purpose of this study was to analyze the implementation of the farmer card program on the availability of fertilizer in 2021 in Tegalmojo village, Tegalsiwalan district, Probolinggo district based on the size and objectives of the policy, resources, characteristics of implementing agents, communication, disposition, and the economic, social, political and environmental factors. the obstacle.. The type of research used is descriptive with a qualitative approach. The subjects of this study consisted of the village head of Tegalmojo, the head of the farmer group. Data collection techniques used in the form of interviews, observation, and documentation. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of this study indicate that the implementation of the Kartu Tani program on the availability of fertilizer in 2021 in Tegalmojo village is quite good but cannot be redeemed using the Kartu Tani due to several obstacles faced.